Relation of Helicobacter Pylori and Hyperemesis Gravidarum in sample of pregnant women in Maternity Teaching Hospital of Erbil city - Linda Sabah Shahab; Awat Ibrahim Hamadamin (Advanced Medical Journal)
Background and objectives: Nausea and vomiting in early pregnancy are accompanied by great impact on general health status of pregnant women especially if presented as hyperemesis gravidarum. The helicobacter pylori infection is predominant in Iraqi community. The aim of the study is to find out whether sero-positivity for immunoglobulin G antibodies to Helicobacter pylori is related to hyperemesis gravidarum.